Advantages and Disadvantages of Mammography Screening - Heywang-Köbrunner, Sylvia H. (S. Karger GmbH, 2011)
Mammography screening is the only method presently considered appropriate for mass screening of asymptomatic women. Its frequent use, however, warrants diligent analysis of potential side effects. Radiation risk is far below the natural yearly risk of breast cancer and should not be used as an argument against screening. False-positive calls lead to additional imaging or histopathological assessment, mainly percutaneous breast biopsy. These measures are tolerated and accepted fairly well. Their number is limited by strict quality assurance and constant training. Interval cancers represent a limitation of breast screening that should prompt further research for optimization. Evaluation of overdiagnosis is a highly debated topic in the literature. According to the probably most realistic available calculations, overdiagnosis is acceptable as it is compensated by the potential mortality reduction. Nonetheless, this potential side effect warrants optimal adjustment of therapy to the patient's individual risk. The mortality reduction seen in randomized studies was confirmed by results from national screening programs. A recent case referent study indicated that improvements in mortality reduction run parallel to improved mammographic techniques. Use of less aggressive therapies is another valuable effect of screening. Awareness of potential problems, strict quality assurance, and further research should help to further develop screening programs.